Synthesis conditions and characterization of superparamagnetic iron oxide nanoparticles with oleic acid stabilizer - Anggita Dipika Wulandari; Sutriyo Sutriyo; Ratika Rahmasari (Journal of Advanced Pharmaceutical Technology & Research, 2022)
Superparamagnetic iron oxide nanoparticles (SPIONs), part of magnetic nanoparticles, have been widely used in biomedical applications. Biocompatibility and magnetic properties make the SPIONs developed further by a lot of researchers. However, in the synthesis process, SPIONs can run into agglomeration. Oleic acid (OA) is one of the stabilizers to prevent agglomeration. This research aims to optimize the synthesis conditions and characterization of SPIONs with OA as a stabilizer. The synthesis of Superparamagnetic Iron Oxide Nanoparticles-Oleic Acid (SPIONs-OA) was performed using the coprecipitation method and was prepared with the addition of 0.75, 1.5, and 3%v/v OA and stirring rate of 750, 1500, 3000, 6000, 9000, and 12,000 rpm. The characterization of hydrodynamic size and polydispersity index was evaluated by dynamic light scattering. Meanwhile, the crystal structure was observed by X-ray diffraction. Then, Fourier transform infrared spectroscopy (FTIR) was used to analyze structures. The results showed that the hydrodynamic size was dependent on OA concentrations and stirring rate. The addition of 1.5%v/v OA and stirring conditions of 750 rpm resulted in the smallest hydrodynamic size and polydispersity index (83.71 ± 0.70 nm and 0.215 ± 0.01 nm, respectively). Based on the crystal structure analysis, the crystal shape was magnetic cubic, and the size of Fe3O4 crystallite changed from 11.38 to 5.61 nm. The FTIR indicated a strong chemical bond between the hydroxyl group of SPIONs and carboxylic acid of OA. In conclusion, the SPIONs-OA was successfully prepared with 1.5%v/v OA concentrations and a stirring rate of 750 rpm.